Application of thermal imaging in primate studies in The Lower Kinabatangan Wildlife Sanctuary, Sabah - Amaziasizamoria Jumail (2020)
Estimating primate populations is critical for many fields of biology. Many studies base their findings on the underlying population density and the primate species abundance. It is crucial to have a method that can improve accuracy whilst reducing bias when conducting primate surveys. The behaviour of diurnal primates which are actively moving during the day, makes it difficult for researchers to accurately estimate number of animals. Then again, night time studies are largely limited by poor visibility. Therefore, this study aims to assess the potential of thermal imaging technique in primate census and surveys and behavioural studies. The objectives of this study are: 1) to optimise the thermal camera technology, 2) to assess the usefulness of thermal camera technology as a handheld tool to estimate primate populations by comparing the thermals surveys with visual surveys, 3) to explore the potential of thermal camera used in primate detection by mounting it on an unmanned aerial vehicle (UAV) and 4) to explore the potential of thermal imaging in primate behaviour studies. Census surveys were conducted along the riverbank early morning for 38 days using two techniques: thermal imaging followed by direct observation by eye. A cumulative total number of 138 primate groups were detected throughout the study. A Wilcoxon signed rank test showed that the use of a handheld thermal camera counted or detected 1. 78 times more primates than counting by eye despite some limitations of using the thermal camera (p=0.000). For the aerial surveys, this technique was able to detect primates using a thermal camera mounted on a drone. The comparison surveys showed all three aerial surveys detected the same number of primates as the thermal camera used as a handheld tool (10, 11, and 17 proboscis monkeys detected respectively). Lastly, overnight behavioural observations were conducted to study the movements of primates during the night in three categories: locations with only long-tailed macaques present, with proboscis monkeys only, and with groups of proboscis monkeys and long-tailed macaques in proximity. Observations were done using the thermal camera by recording continuously from 6:00pm to 6:00am. Overnight observations showed no significant activities recorded from all three categories. The results of this study show the utility of a thermal imaging technique applied in primate surveys and behavioural studies. Therefore, the use of thermal imaging in combination with a conventional visual census can provide more accurate estimates of species identity and primates counts, and also contribute to behavioural studies.